Erratum to: A-priori Estimates Near the Boundary for Solutions of a class of Degenerate Elliptic Problems in Besov-type Spaces; DOI 10.1515/mjpaa-2017-0013 - Azzeddine El Baraka; Mohammed Masrour (Moroccan Journal of Pure and Applied Analysis, 2018)
Abstract In this note, we point out some minor errors found in [1] and we give the proper corrections.